The effect of organizational culture and organizational commitment on employee performance at Bank CIMB Niaga Tbk Branch Pondok Gede Bekasi - Nyoman Suardhita; Ahmad Rafik; Otto Siregar (Privietlab, 2021)
This study aims to determine and analyze the performance of employees at Bank CIMB NIAGA, Tbk Pondok Gede Branch, Bekasi. In this regard, how employees can work well with the influence of organizational culture and organizational commitment. So against this, this study aims to show the significance of the influence of organizational culture and organizational commitment on employee performance. The number of samples used as many as 56 people using population research theory in taking samples. Data collection was done by using a questionnaire method. The data analysis technique used is multiple linear regression analysis using Statistical Product and Service Solution (SPSS). Multiple linear regression equation produces the equation Y = 9.157 + 0.151 X1 + 0.641 X2. The results of this study found that the variables (organizational culture and organizational commitment) simultaneously affect work motivation and the value of F Calculate (41.550) > F-Table (3.172). The results of the correlation analysis of determination (R Square) of 0.611 indicate that the variables of organizational culture and organizational commitment can contribute 61%. 39% influenced by other variables not examined. The most dominant variable affecting performance is the organizational commitment variable between the two variables with a t-count value (5.141) > t-table (2.005). While the organizational culture variable is not significant with the value of count (1.098) < t-table (1.672).